Predictive management tools as support for the internationalization of agricultural enterprises in the Republic of Moldova - Ulinici, Andrian (Актуальні питання економічних наук, 2026)
The relevance of the study is driven by increasing volatility of global agricultural markets, intensifying competition, and the strong dependence of the agricultural sector of the Republic of Moldova on external factors, which necessitates the improvement of management tools for internationalization processes. The aim of the article is to substantiate the role of predictive management tools in supporting the entry of agricultural enterprises into international markets. The methodological framework is based on systemic and comparative analysis, generalization of statistical data, and econometric modelling. The empirical base is formed using data from international organizations and national statistics for the period 2018–2024. Correlation analysis and the SARIMA model were applied to analyse indicator dynamics and generate forecasts, allowing for the consideration of seasonal and trend components. The study finds that agricultural exports largely depend on external price factors and macroeconomic conditions, while the influence of production indicators remains limited. A pronounced seasonality and instability of export flows are identified. The developed model demonstrates satisfactory forecasting accuracy and the ability to capture key patterns of sectoral development. It is proven that the use of predictive tools enhances the validity of managerial decisions, reduces uncertainty, and facilitates the adaptation of strategies to changes in the external environment. The conclusions emphasize that the implementation of predictive approaches is an important condition for increasing the competitiveness of agricultural enterprises and improving the effectiveness of their internationalization. At the same time, certain limitations are identified, related to the use of aggregated data and classical models, which outlines directions for further research.